Which Expression Represents The Volume, In Cubic Units, Of The Composite Figure?

WILL GIVE BRAINLIEST Which expression represents the volume, in cubic units, of the composite figure? A. (8)(6)(6) + (8)(6)(4)B. (8)(6)(10) + (8)(6)(4)C. (8)(6)(4) – (8)(6)(6)D. (8)(6)(4) – (8)(6)(10)

Solution:

The figure is splitted into two shapes.

One is rectangular pyramid and the other is rectangular prism.

Rectangular pyramid:

Length = 8

Width = 6

Height = 10 – 4 = 6

Volume of rectangular pyramid =

Volume of rectangular pyramid

Rectangular prism:

Length = 8

Width = 6

Height = 4

Volume of rectangular prism = length × width × height

= 8 × 6 × 4

Volume of rectangular prism = (8)(6)(4)

Volume of figure = Volume of pyramid + volume of prism

The volume of the composite figure is cubic units.

“Let”s see if it works with the two consecutive integers 5 and 6:

let x = 5

so x + 1 = 6

5 + 6 = 11, so:

2x + 1 = 11

2x = 10 (subtracted 1 from both sides)

x = 5 (divided both sides by 2)

it works!”

represent the sequence 16,24,32,40…

Step-by-step explanation:

The sequence given is

16,24,32,40.

And the options given are

an=4n+1

an=8n+8

an=8n+16

We will check for all so as to find the correct expression.

In the given sequence the first term is 16,

i.e a1 = 16

1). We will check for an = 4n+1 whether the first term is 16 or not.

We will put the value of n as 1;

With this option we get the first term as 5 but in the given sequence first term is 16.

Hence this option is Incorrect.

2). We will check for an = 8n+8 whether the first term is 16 or not.

We will put the value of n as 1;

With this option we get the first term as 16 and in the given sequence also first term is 16.

Hence this option is correct.

3). We will check for an = 8n+16 whether the first term is 16 or not.

We will put the value of n as 1;

With this option we get the first term as 24 but in the given sequence first term is 16.

Hence this option is Incorrect.

Hence we can say that an = 8n+8 represent the sequence 16,24,32,40…

D. 6x³ + 5x² – 3x – 2

Step-by-step explanation:

First assign each variable with its number.

l = 2x + 1

w = x + 1

h = 3x – 2

Now, plug in.

v = (2x + 1)(x +1)(3x – 2)

Now combine the first two pairs following the FOIL method. (First Outer Inner Last)

(2x² + 3x + 1)(3x – 2)

Now you would multiply the 3x on to each term and the -2 on to each term.

6x³ + 9x² + 3x – 4x² – 6x – 2

Now combine like terms.

6x³ + 5x² – 3x – 2

p:20

p:25

Step-by-step explanation:

Comment

Name *

Email *

Website

Save my name, email, and website in this browser for the next time I comment.

Δ

Related Posts
Math
The diameter of a sphere is 4 centimeters. Which represents the volume of the sphere?
October 25, 2021 thanh
Math
Find the solutions for a triangle with a=16, c=12, b=63, b=63°
October 25, 2021 thanh
Search for: